1994
DOI: 10.1152/ajpgi.1994.266.2.g247
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress induces S-thiolation of specific proteins in cultured gastric mucosal cells

Abstract: Oxidative stress induces the formation of protein-mixed disulfides with low-molecular-weight thiols, especially glutathione. We analyzed this process, termed S-thiolation, in cultured gastric mucosal cells from guinea pigs by gel electrophoresis and autoradiography after radiolabeling of the intracellular glutathione pool with 35S. Hydrogen peroxide (H2O2) or diamide initiated rapid and reversible S-thiolation of specific proteins with molecular masses of 42, 30, 29, 28, and 22 kDa. Diamide caused particularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 0 publications
0
58
0
Order By: Relevance
“…The accumulation of glutathionylated proteins is an indicator of protein oxidation arising from the formation of hydrogen peroxide [30,20,2]. The rise of 4-HNE signals lipid peroxidation, mainly due to the production of hydroxyl radical, and 3-NT suggests peroxynitrite reactions [26].…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of glutathionylated proteins is an indicator of protein oxidation arising from the formation of hydrogen peroxide [30,20,2]. The rise of 4-HNE signals lipid peroxidation, mainly due to the production of hydroxyl radical, and 3-NT suggests peroxynitrite reactions [26].…”
Section: Discussionmentioning
confidence: 99%
“…Male guinea pigs weighing ‫ف‬ 250 grams were purchased from Japan SLC Inc. (Shizuoka, Japan). Gastric mucosal cells were isolated aseptically from fundic glands and cultured for 2 d in RPMI 1640 containing 10% FCS, 2 mM glutamine, 100 g/ml streptomycin, and 100 U/ml penicillin, as described previously (7,17). The periodic acid-Schiff reaction showed that Ͼ 85% of the cultured cells were mucus secreting (7,17).…”
Section: Methodsmentioning
confidence: 99%
“…The contents of reduced glutathione (GSH) and its disulfide (GSSG) in cultured cells were measured as described previously (17). Briefly, acid-soluble thiols were extracted by treating the cells in 35-mm-diameter culture dishes with 200 l of 5% perchloric acid containing 2.5 mM o -phenanthroline for 30 min on ice.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One modification of cysteine residues that takes place in cells is reversible disulphide bond formation with the cellular thiol, glutathione (termed glutathiolation) [1][2][3]. A number of studies indicate that the glutathiolation of cellular proteins (glyceraldehyde-3-phosphate dehydrogenase, BSA, haemoglobin, nuclear factor 1) can be reversed in itro in the presence of the cellular enzyme thioltransferase (glutaredoxin) [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%